When is life not in our own best interests? The best interests test as an unsatisfactory exception to the right to life in the context of permanent vegetative state cases. (March 2013) - Wicks, Elizabeth
This article investigates the relationship between the application of the best interests test in respect of the withdrawal of life-sustaining treatment and the positive obligation under the right to life. It argues that the superficial reconciliation of the concepts of best interests and the right to life in English case law fails to adequately protect the right to life of incompetent patients, while also failing to afford sufficient protection to a patient's personal perception of human dignity. It argues that greater recognition should be given both to the obligations placed upon the state, by domestic and international human rights law, to take reasonable steps to preserve life as well as to the need to incorporate subjective values into the statutory test of best interests.